Homeopathic Management of Hypothyroidism: A Case Series Study - Dr Maneesha Soni (The Bioscan, 2024)
Hypothyroidism is a common endocrine disorder that affects metabolic processes in the body. Conventional treatment includes synthetic thyroxine supplements, but homeopathic remedies have been gaining attention for their individualized, holistic approach. This study presents a series of hypothyroid cases treated at KEMT Virar Homoeopathic College and OPD using homeopathic remedies. It evaluates their outcomes based on clinical improvement and thyroid function test results.